Analisis Pendapatan dan Kelayakan Usahatani Jagung Hibrida - Fadil, Muhammad; Fitriana, Widya; Khairati, Rusda (Universitas Galuh, 2025)
Hybrid corn has high productivity and contributes to the growth of the animal feed industry. However, farmers' use of hybrid corn varieties still needs improvement. Farmers have complained about the relatively high price of hybrid corn seeds. Pesisir Selatan Regency is one of the leading corn producers in West Sumatra. In 2022, the corn production reached 203,028.00, the second highest after West Pasaman. However, the productivity is only 6 tons/ha, which is still low compared to the potential productivity of hybrid corn, which is 10-12 tons/ha. The productivity achievements are related to the technical culture farmers apply and their income and feasibility. This study aims to (1) describe the technical culture of hybrid corn and (2) analyze the income and feasibility of hybrid corn farming. The research was carried out in the